Refraction development in anisometropic amblyopia with patching therapy - Chen, Yao; Zuo, Jingjing; Xiong, Yue; Yu, Xi; Wei, Lili; Luo, Yifan; Bao, Jinhua; Chen, Hao; Zhou, Jiawei (Frontiers in Medicine, 2022)
Purpose: To investigate the development of refraction in anisometropic amblyopia who had been with patching therapy. Methods: We retrospectively reviewed 37528 medical records of the amblyopes who had been treated with patching therapy between July 2003 and January 2020 at the School of Optometry and Ophthalmology and Eye Hospital of Wenzhou Medical University. We included unilateral anisometropic amblyopia with a follow-up length of not less than 2 years. In total, 371 cases were enrolled and followed up for a mean of 4.76 ± 2.11 years. The subjects were then divided into different groups and periods according to their initial spherical equivalent (SE) refractive error and best-corrected visual acuity (BCVA) of the amblyopic eye. Linear mixed-effects models were fit to calculate the annual change of SE. Results: The annual changes in SE were -0.32 (-0.35 to -0.30) D/yr and -0.16 (-0.19 to -0.14) D/yr for the amblyopic eye and the fellow eye, respectively. The annual changes in SE of amblyopic eyes during the treatment period and the successfully treated period were -0.36 (-0.43 to -0.29; 95% CI) D/yr and -0.27 (-0.32 to -0.23; 95% CI) D/yr, respectively; the annual SE changes of the fellow eye during the treatment period and the successfully-treated period were -0.07 (-0.14 to -0.01; 95% CI) D/yr and -0.18 (-0.22 to -0.14; 95% CI) D/yr, respectively. Conclusion: The amblyopic eye experienced a significantly greater degree of refractive error changes than the fellow eye and underwent a continuous refractive error reduction before and after 7 years old. After the patching therapy was terminated, emmetropization in the amblyopic eye remained synchronized, whereas the refractive error change was increased in the fellow eye.